Investigation of local materials on the durability of energy generating biomass cook stove for rural settlers - M.E, Moses; O.D, Okonkwo; Quincy S, Jack (International Journal of Engineering and Technology, 2018)
Energy demands in rural communities of developing countries are relatively low. The objective of this work is to provide a smart energy generation from available local materials. Biomass cook stoves are used in most rural communities in developing countries. Its durability and mode of pollution dispersion remains a major challenge. In this research, biomass cook stove was constructed using different local ma-terials. The heat sink sources that were used are steel, copper, iron and low grade steel. Two focuses of the research were the compatibility of the local materials to the thermoelectric (TE) module and its influence on the corrosion of its heat sink. The design specification of the biomass cookstove was to limit environmental pollution and control airflow to the biomass fuel. It was observed that the thermal effect on the heat sink has great influence on the thermoelectric module. The challenge of recurrent results in past research was resolved by the intro-duction of image analyzer to examine the thermal corrosion on the heat sink. The challenges facing the durability of the improved biomass cook-stove were highlighted in the study for further study.Â Â